2015
DOI: 10.14260/jemds/2015/800
|View full text |Cite
|
Sign up to set email alerts
|

360 Degree Subannular Tympanoplasty: A Retrospective Study

Abstract: OBJECTIVE OF THE STUDY:To study the efficacy of underlay tympanoplasty by elevating the annulus by 360 degrees. SUBJECTS AND METHODS: Two hundred patients with chronic otitis media, tubotympanic disease, inactive stage who underwent tympanoplasty by the above technique between the years 2009 to 2013 were selected for the study as and when they were admitted. All the patients were followed up for 6 months following surgery. Any complications like secondary infection, wound dehiscence, granulations, were looked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…16 Moras et al reported 3% of anterior blunting. 28 Mokhtarinejad et al, Pradhan et al did same flap technique as ours and didn't encounter any blunting or lateralization of graft. 15,3 Jung et al did mediolateral graft tympanoplasty and noticed one patient with anterior blunting.…”
Section: Anterior Bluntingmentioning
confidence: 58%
“…16 Moras et al reported 3% of anterior blunting. 28 Mokhtarinejad et al, Pradhan et al did same flap technique as ours and didn't encounter any blunting or lateralization of graft. 15,3 Jung et al did mediolateral graft tympanoplasty and noticed one patient with anterior blunting.…”
Section: Anterior Bluntingmentioning
confidence: 58%
“…[15][16][17] There are numerous studies highlighting the problematic anterior quadrant perforation repair for which several modified techniques and methods have been incorporated like the Gerlach quilt method, anterior hitch method, Kerr flap technique, 360degree subannular tympanoplasty, anterior interlay myringoplasty, window shade technique, circumferential flap method and anterior tucking technique. [18][19][20][21][22][23][24] In the literature, tympanoplasty with anterior tucking by a microscopic postauricular approach using temporalis fascia had success rates varying from 88% to 98%. 25,26…”
Section: Introductionmentioning
confidence: 99%